(3QSGdI aj JMbjb ePgH GHf SjfGs - (3Ydj Hf aVd Gddg GdLjdGfj Gdahdj GdRGgOjs ((3eMeO aGQhb GdGfUGQi s)
(3ChdgG (B:s
(3GdMeO ddg EjeGfkG dhMOGfjJg hEbQGQkG dUeOGfjJg hGdTcQ Ydi EJeGe fYeJg CeG HYO ajbhd bO hbYJ ai eMdS HYV GdSGOGJ GdcQGe TQY HYVge HGdebGd HChUGa Cgd GdaVd hGdMGd ef GdSda hGdNda s
(3BNQgG (B:s
(3hcGO Gf jchf ef GdegJOjf Ef de jcf ef GdeYGfOjf GdVGdjf GdeVdjf hdGMhd hdG bhI EdG HGddg GdYdi GdYXje s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI YdjcQI (B((3YQHjI (B15) s
Keywords: (3GdadSaI hGdefWbs